1. Let the [tex]n^{th} [/tex] term of the sequence be [tex] u_{n} [/tex]
2. The first term [tex]u_{1} [/tex]=1/27, second term [tex]u_{2} [/tex]=1/9 and so on
3. so
[tex]u_{1}= \frac{1}{27}= \frac{1}{ 3^{3} }= 3^{-3} [/tex]
[tex]u_{2}= \frac{1}{9}= \frac{1}{ 3^{2} }= 3^{-2} [/tex]
[tex]u_{3}= \frac{1}{3}= \frac{1}{ 3^{1} }= 3^{-1} [/tex]
[tex]u_{4}= 3^{0} [/tex]
so by now it is clear that the general rule is [tex]u_{n}= 3^{n-4}[/tex]
so the next term, [tex]u_{4}[/tex] is [tex]u_{5}= 3^{5-4}=3^{1}=3[/tex]